1992
DOI: 10.1254/jjp.59.201
|View full text |Cite
|
Sign up to set email alerts
|

Active Cutaneous Anaphylaxis (ACA) in the Mouse Ear

Abstract: ABSTRACT-Active cutaneous anaphylaxis (ACA) was studied in the ear of female BALB/c mice. Mice were immunized with ovalbumin in the presence of aluminium hydroxide gel or complete Freund's adjuvant (CFA). Two weeks after the immunization, ACA was elicited in the mouse ear by injecting 10,ul of antigen solution intradermally into the ear lobe. ACA was assessed by the amount of extravasated dye, which was given intravenously just after the antigen injection. Antiallergic drugs (tra nilast, ketotifen and azelasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…Con, control (sensitized mice); L-92: L-92-treated sensitized mice; Tac, tacrolimus-treated sensitized mice; Veh, vehicle (non-sensitized mice). gic reactions, active sensitization plays a more significant role in the pathogenesis of allergic diseases (31). However, similar to the PCA response, L-92 potentially inhibited the vascular permeability increase caused by ACA and production of OVA-specific IgE in comparison with the control mice.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Con, control (sensitized mice); L-92: L-92-treated sensitized mice; Tac, tacrolimus-treated sensitized mice; Veh, vehicle (non-sensitized mice). gic reactions, active sensitization plays a more significant role in the pathogenesis of allergic diseases (31). However, similar to the PCA response, L-92 potentially inhibited the vascular permeability increase caused by ACA and production of OVA-specific IgE in comparison with the control mice.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, L‐92 may suppress IgE‐dependent mast cell activation and/or antagonize against histamine action. Although passive sensitization is suitable for analysis of allergic reactions, active sensitization plays a more significant role in the pathogenesis of allergic diseases (31). However, similar to the PCA response, L‐92 potentially inhibited the vascular permeability increase caused by ACA and production of OVA‐specific IgE in comparison with the control mice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, participation of mast cells in CH has been suggested (44), and a defective CH was demonstrated in mast cell-deficient mice (45). Because activation of mast cells is important in PCA and the degree of PCA can be estimated by measuring the amount of extravasated dye in the reaction site (31,32,46,47), we examined the effect of PAR-2 deficiency on the increased dye content after ear PCA. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The cutaneous antigen challenge of previously sensitized mice triggers mast cell activation and degranulation, release of vasoactive mediators, increase in vascular permeability, and dye extravasation. Mast cell stabilizers like sodium cromoglycate, antihistamines (H 1 receptor blockers), and glucocorticoids given over longer periods have been found to reduce this allergic reaction [ 36 ]. In the classic ACA study by Inagaki et al (1992), mast cell stabilizers and antihistamines were shown to be effective when given in a short period while steroids showed effect when given 8 h prior to allergen challenge.…”
Section: Discussionmentioning
confidence: 99%